A new pearlfish, Onuxodon albometeori sp. nov. (Ophidiiformes: Carapidae), from Taiwan - Koeda, Keita (Zootaxa, 2019)
Onuxodon albometeori sp. nov. (Ophidiiformes: Carapidae) is described from a single specimen collected by commercial trawl off southwestern Taiwan. The new species is most similar to the Indo-Pacific species Onuxodon fowleri (Smith 1955), both process a remarkably slender body, and higher precaudal vertebral counts and a longer pectoral fin, although the two latter features are even more extreme in the former. Onuxodon albometeori sp. nov. is further distinguished from O. fowleri by its lesser body depth, greater head width, higher counts of precaudal vertebrae, and uniformly whitish coloration only on the posterior part of the body.